A new approach in coronary interventional cardiology: the distal radial approach - Danthine, P; Maréchal, P; Lancellotti, P (Revue médicale de Liège, 2022)
The conventional radial approach has become the access route of choice for performing diagnostic or therapeutic coronary angiography. It has taken precedence over the femoral approach, which is subject to a higher rate of vascular and hemorrhagic complications. The distal radial approach is currently considered a further refinement of the conventional radial approach. It offers the advantage of potentially reducing local vascular complications (spasm, thrombosis of the radial artery), of allowing rapid mobilization of the wrist (hemostatic band against the scaphoid), of reducing the duration of hemostasis, and of preserving the proximal radial artery for future procedures such as arteriovenous bypasses or shunts. The use of the left distal radial access also makes it possible to avoid the restriction of the movements of the right hand after the catheterization, to improve the comfort of the operator during the procedure and to reduce exposure to radiations, as well as to offer the possibility of performing angiography in patients who have already undergone bypass surgery with the left internal mammary artery graft (LIMA).